Neighborhood Context and Perceptions of Stress Over Time: An Ecological Model of Neighborhood Stressors and Intrapersonal and Interpersonal Resources. Issue 3 (12th February 2013) - Brenner, Allison B.; Zimmerman, Marc A.; Bauermeister, Jose A.; Caldwell, Cleopatra H.
Abstract: We examine the association between neighborhood socio‐economic disadvantage and perceived stress during middle and late adolescence among African American youth (N = 665; 51 % female; M = 15.9 years at baseline). In addition, we explored the ways through which neighborhood stressors interacted with an individual's intra‐ and interpersonal resources (e.g., coping, social support and substance use), to affect their perceived stress trajectories during adolescence. First, we tested a neighborhood stressors model and found that youth who lived in neighborhoods with greater socioeconomic disadvantage had higher baseline stress and a steeper increase in stress over time. When we included individual‐level risk and promotive factors in the model, however, the effect of neighborhood disadvantage on perceived stress was no longer significant, and the stress trajectory was explained by adolescent substance use, social support and perceptions of the neighborhood. Our results support theories of stress and coping, and the importance of proximal intra‐ and interpersonal factors in either amplifying or mitigating perceptions of stress. We discuss implications of the neighborhood context and how our findings may inform future prevention and intervention related to adolescent stress and development.